The Phenomenon of Digraphia In Islamic Education: Students’ Use of Arabic-Malay (Jawi) Script at Thamavitya Mulniti School In Yala, Thailand - Rizki Hapizahtun Nisa; Syaukani Syaukani (Jurnal Eduslamic, 2026)
This study was motivated by the discovery of the phenomenon of digraphia in Arabic language learning. Efforts to preserve identity take the form of using two writing systems Arabic Malay (Jawi) and Standard Arabic in Arabic language instruction; the preservation of identity in question refers to the preservation of the Malay Islamic identity found in southern Thailand. The objective of this study is to identify the causes of the digraphia phenomenon and to examine the implementation of the use of Arabic-Malay (Jawi) in Arabic language learning. The research method employed is a qualitative research method using a phenomenological approach, with data collection techniques including observation, interviews, and documentation. The results of this study indicate that the phenomenon of digraphia occurs due to the active use of two languages in Southern Thailand Thai and Malay and that Arabic-Malay is chosen as a secondary script to aid in the Arabic language learning process. The implementation of the Arabic-Malay (Jawi) script facilitates students’ learning of Arabic from writing and reading skills to the ability to communicate in Arabic.